THE PROTECTION OF CHILDREN’S WELFARE IN UNDERAGE MARRIAGE UNDER THE SYARIAH LAW IN MALAYSIA: AN APRAISAL ANALYSIS (SALAM Digest: Syariah and Law Undergraduate Symposium, 2024)
This study examines the protection of children's rights in Malaysia by evaluating underage marriage within the framework of Islamic principles and Syariah Law. Between 2013 and 2018, the Malaysian Syariah Judicial Department recorded 5,823 applications for underage marriage, with 1,856 cases approved by the Syariah Courts. These statistics highlight weaknesses in the judicial system and legal provisions concerning underage marriage and the welfare of affected children. This research adopts a qualitative approach, utilizing library research and content analysis methods to analyze legal provisions, explore Islamic perspectives, and emphasize the need for comprehensive strategies aligned with Syariah principles. The findings stress the importance of strengthening child welfare protections through targeted education, healthcare initiatives, strict enforcement of existing laws, and awareness campaigns to combat child marriage in Malaysia.